2010
DOI: 10.1002/0471140856.tx2109s46
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Gastrointestinal Propulsive Activity Using Three Different Models of Peristalsis In Vivo in the Mouse

Abstract: The protocols described in this unit are designed to assess the acute effects of drugs on the propulsive activity of the gastrointestinal muscles in the conscious mouse. These protocols are currently applied to investigate the pharmacological activity of novel compounds undergoing preclinical development and to obtain predictive data needed to advance drugs into clinical trials. Moreover, these methods could be useful in evaluating the functional toxicity by environmental or alimentary pollutants, like xenobio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In vivo studies measure the regional transit times, like gastric emptying and intestinal or whole gut transit 3,5 . Studies also employed advanced imaging techniques to measure GI transit, including scintigraphy, ultrasound, CT, MRI, and radiography 6‐8 . Still, an inexpensive and readily available dye transit measurement of "leading edge" whole gut transit remains the gold‐standard 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies measure the regional transit times, like gastric emptying and intestinal or whole gut transit 3,5 . Studies also employed advanced imaging techniques to measure GI transit, including scintigraphy, ultrasound, CT, MRI, and radiography 6‐8 . Still, an inexpensive and readily available dye transit measurement of "leading edge" whole gut transit remains the gold‐standard 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Another potential limitation was that residual food content in the gut at the time of the experiments would have affected GIP secretion. However, it has been shown that gastrointestinal transit time in mice is such that 80% has passed through after 60 min 39 , which suggests that this effect is probably minor in the present experiments in which the mice were fasted for 2 h.…”
Section: Discussionmentioning
confidence: 53%